ASSOCIATION OF SURGICAL APGAR SCORE WITH POSTOPERATIVE MORBIDITY AND MORTALITY IN HIP FRACTURES: A PROSPECTIVE COHORT - RAFIQ , SU; AHMAD , T; MARIAM , F; JAMAL , S; KHAN, MAG; SULAIMAN , MA (Biological and Clinical Sciences Research Journal, 2024)
Hip fractures are mostly associated with post-operative morbidity and mortality. The Surgical Apgar Score considers the intraoperative parameters for risk estimation of postoperative complications or mortality. Objective: To assess the association of surgical Apgar score with postoperative morbidity and mortality among patients with hip fractures. Methods: Thirty-eight patients of both genders aged≥18 years who underwent hip fracture surgery were included. Surgical Apgar Score (SAS) is based on intra-operative values of lowest heart rate (LHR), lowest mean arterial blood pressure (LMAP), and estimated blood loss (EBL). Mortality within 30 days of surgery was recorded. The normality of data was checked, and the Median (IQR) was reported due to non-normal distribution. Frequencies and percentages were calculated for qualitative variables. Mann Whitney U-test was applied to study the association between SAS and postoperative complications. P-value ≤0.05 was considered as statistically significant. Results: Median age was 71 years [(IQR) 62.25-76.25]. Thirty-seven percent of patients were male, and 63.2% were female. Four patients (10.5%) experienced cellulitis, wound dehiscence, aspiration pneumonia, and the onset of supraventricular tachycardia during the post-operative phase. Four patients (10.5%) required readmission. 11 patients (28.9%) were retained in special care units for one to two days. The median surgical APGAR score was 7[(IQR) 6-8] in relation to the operating parameters. No statistically significant difference was discovered between the complication and the Apgar score (p=0.060). Conclusion: The Surgical Apgar score does not help predict the postoperative risk of complications and 30-day mortality after hip surgeries.